2013
DOI: 10.1039/c2lc41266g
|View full text |Cite
|
Sign up to set email alerts
|

A doubly cross-linked nano-adhesive for the reliable sealing of flexible microfluidic devices

Abstract: Along with the expansion of microfluidics into many areas of applications such as sensors, microreactors and analytical tools, many other materials besides poly(dimethylsiloxane) (PDMS) have been suggested such as poly(imide) (PI) or poly(ethylene terephthalate) (PET). However, the sealing methods for these materials are not reliable in that many of the methods are specific to the substrate materials. Here, we report a novel robust doubly cross-linked nano-adhesive (DCNA) for bonding of various heterogeneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…In addition to the photoresist 25 bonding described above in the materials section, a doubly cross-linked nano-adhesive was demonstrated to improve the bonding between any combination of PDMS, glass, silicon, polyimide and poly(ethylene) terephthalate (PET). 26 This promising coating was vapor deposited in a 200nm layer and the bond strength was at least 2.5 MPa in all cases. PDMS was also bonded to a biologically friendly photoresist poly(2,2-dimethoxy nitrobenzyl methacrylate-r-methyl methacrylate-r-poly(ethylene glycol) methacrylate) (PDMP) using a mussel inspired poly(dopamine) adhesion layer.…”
Section: Fundamentalsmentioning
confidence: 98%
“…In addition to the photoresist 25 bonding described above in the materials section, a doubly cross-linked nano-adhesive was demonstrated to improve the bonding between any combination of PDMS, glass, silicon, polyimide and poly(ethylene) terephthalate (PET). 26 This promising coating was vapor deposited in a 200nm layer and the bond strength was at least 2.5 MPa in all cases. PDMS was also bonded to a biologically friendly photoresist poly(2,2-dimethoxy nitrobenzyl methacrylate-r-methyl methacrylate-r-poly(ethylene glycol) methacrylate) (PDMP) using a mussel inspired poly(dopamine) adhesion layer.…”
Section: Fundamentalsmentioning
confidence: 98%
“…They reported compatibility with working pressures up to 10 MPa for chips sealed at 60°C. Very recently, a doubly crosslinked nano-adhesive was introduced by You et al, wherein they deposited 200 nm of epoxy-containing polymer on various substrates via chemical vapor deposition and reported a maximum burst pressure of 11.7 MPa after curing the film at 70°C for 5 h [118].…”
Section: Sealing Using Adhesive Layersmentioning
confidence: 99%
“…We noted that You et al, [ 25 ] which investigated cross-linking of PGMA interfaces using ethylene diamine, commented that some of the adhesive characteristics might stem from reaction directly between the epoxy groups (they annealed samples at 70 °C for 5 h). Considering that we, in our thermal degradation data, see no evident crosslinking in PGMA samples annealed under similar conditions ( Figure S7, Supporting Information), the amine-epoxy interface reaction is likely the main contributing factor for their observed results.…”
Section: Transitions In Film Adhesive Properties Characterized By Posmentioning
confidence: 97%
“…Previous efforts using iCVD polymer fi lms as adhesives have either involved a reaction at the interface between complementary functional groups on PGMA and polyaminostyrene (PAS) fi lms respectively, or by introducing small cross-linker molecules to create a bond. [ 23,25 ] However, numerous studies have shown that the adhesion between poorly miscible polymers, such as PGMA-PAS, or use of short linkers (ethylene diamine) are generally weak due to poor chain diffusion and localized stress concentration. [ 29,[42][43][44] The symmetric PGMA-PGMA interface employed in our studies enables diffusion and chain entanglement of polymer chains between the fi lms, which are important factors to realize higher adhesion energies.…”
Section: Transitions In Film Adhesive Properties Characterized By Posmentioning
confidence: 99%
See 1 more Smart Citation